Single Cell Transcriptomics Implicate Novel Monocyte and T Cell Immune Dysregulation in Sarcoidosis - Garman, Lori; Pelikan, Richard C.; Rasmussen, Astrid; Lareau, Caleb A.; Savoy, Kathryn A.; Deshmukh, Umesh S.; Bagavant, Harini; Levin, Albert M.; Daouk, Salim; Drake, Wonder P.; Montgomery, Courtney G. (Frontiers in Immunology, 2020)
Sarcoidosis is a systemic inflammatory disease characterized by infiltration of immune cells into granulomas. Previous gene expression studies using heterogeneous cell mixtures lack insight into cell-type-specific immune dysregulation. We performed the first single-cell RNA-sequencing study of sarcoidosis in peripheral immune cells in 48 patients and controls. Following unbiased clustering, differentially expressed genes were identified for 17 cell types and bioinformatically assessed for function and pathway enrichment. Our results reveal persistent T cell receptor-mediated activation of effector T cells and innate activation of circulating monocytes with subsequent upregulation of trafficking molecules in sarcoidosis. Specifically, effector T cells show T cell receptor mediated activation as well as enrichment of associated metabolic pathways and regulatory pathways involving PD-1, NFκB, and multiple cytokines. Regulatory T cells demonstrated enrichment of PD-1 and cell death signaling and differential expression of functional genes. Classical and non-classical monocytes upregulated distinct markers of activation including adhesion molecules, pattern recognition receptors including TLR2 and TLR4, and chemokine receptors. Classical monocytes demonstrated enrichment of immunoregulatory pathways PPAR and HOTAIR, while IL-5 and p-selectin were enriched in non-classical monocytes. Using more sensitive technology and more precise units of measure, we identify cell-type specific, novel immune and metabolic pathways characterizing sarcoidosis. We show antigen-driven Th1 T cell response, dysfunctional regulatory T cells, and innate activation and trafficking of circulating monocytes. We further our understanding of the immunopathology of sarcoidosis and point to novel diagnostic markers and potential therapeutic targets.